The interaction between physical activity and obesity gene variants in association with BMI: Does the obesogenic environment matter?. (November 2016) - Graff, M.; Richardson, A.S.; Young, K.L.; Mazul, A.L.; Highland, Heather; North, K.E.; Mohlke, K.L.; Lange, L.A.; Lange, E.M.; Harris, K.M.; Gordon-Larsen, P.
Abstract: Little is known about how obesity susceptibility single nucleotide polymorphisms (SNPs) interact with moderate to vigorous physical activity (MVPA) in relation to BMI during adolescence, once obesogenic neighborhood factors are accounted for. In race stratified models, including European (EA; N=4977), African (AA; N=1726), and Hispanic Americans (HA; N=1270) from the National Longitudinal Study of Adolescent to Adult Health (1996; ages 12–21), we assessed the evidence for a SNPxMVPA interaction with BMI-for-age Z score, once accounting for obesogenic neighborhood factors including physical activity amenities, transportation and recreation infrastructure, poverty and crime. Eight SNPxMVPA interactions with suggestive significance (p<0.10; three in each EA, and AA, two in HA) were observed showing attenuation on BMI-for-age Z score in adolescents with ≥5 versus <5 bouts/week MVPA, except for rs10146997 (near NRXN3 ). Findings were robust to the inclusion of neighborhood-level variables as covariates. These findings suggest that any attenuation from MVPA on a genetic susceptibility to obesity during adolescence is likely not operating through obesogenic neighborhood factors. Highlights: Obesity susceptibility SNPs may interact with physical activity to attenuate increased BMI. The obesogenic environment might change this interaction. We tested the interaction of eight SNPs each with physical activity once the obesogenic neighborhood was accounted for. Neighborhood-level factors did not influence SNPxMVPA interactions. Physical activity may attenuate genetic influences on BMI in any environment.